PEMAKAIAN NORPLANT SECARA SALAH: ANTARA KUALITAS PELAYANAN DAN KEPATUHAN AKSEPTOR - Susi Eja Yuarsi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1998)
The number of norplant users had increased over time, the problem was that many women use norplant incorrectly. Some of them used it longer than five years without removal and some other women used double norplant. Also, there were some women who used one set of norplant with more or less than 6 norplant matchsticks as required. These problems would certainly bring negative effects on women's health and, in turn, their economic condition. At national level, the large number of misusers would cause a failure of the family planning program.Non-compliance behavior among norplant users was caused by many factors. Poor quality of care, especially providers' incompetence, inadequate information, and inadequate mechanisms to encourage continuity were found as major causes. The clients themselves had a contribution in the misuse of norplant. The clients had their own beliefs about health and sickness and they also tend to be influenced by the behavior of their neighbors who were misusing norplant. The clients awareness about the importance of information was also very low and It caused the lack of knowledge about the arrangements of using norplant.